Temperament profiles are associated with dietary behavior from childhood to adulthood. (1st August 2020) - Lipsanen, Jari; Elovainio, Marko; Hakulinen, Christian; Tremblay, Mark S.; Rovio, Suvi; Lagström, Hanna; Jaakkola, Johanna M.; Jula, Antti; Rönnemaa, Tapani; Viikari, Jorma; Niinikoski, Harri; Simell, Olli; et al.
Abstract: Background and objectives: Temperament may be associated with eating behaviors over the lifespan. This study examined the association of toddlerhood temperament with dietary behavior and dietary intervention outcomes across 18 years. Methods: The study comprised 660 children (52% boys) from The Special Turku Intervention Project (STRIP), which is a longitudinal randomized controlled trial from the age of 7 months until the age of 20 years (1990–2010). Temperament was assessed using Carey temperament scales when the participants were 2 years of age. Latent profile analysis yielded three temperament groups, which were called negative/low regulation (19% of the children), neutral/average regulation (52%) and positive/high regulation (28%). Dietary behavior was examined from 2 to 20 years of age using food records, which were converted into a diet score (mean = 15.7, SD 4.6). Mixed random-intercept growth curve analysis was the main analytic method. Results: Dietary behavior showed a significant quadratic U-shaped curve over time (B for quadratic association = 0.39, P <.001; B for linear association = 0.09, P = 0.58). Children in the negative/low regulation temperament group had a lower diet score (less healthy diet) across the 18 years compared to children in the neutral/average or in the positive/high regulation group. Temperament was not associated with the rate of change in diet over time. Temperament did not have any interactive effects with the intervention (F [2, 627], P  = 0.72). Conclusion: Children with a temperament profile characterized by high negative mood, high irregularity and high intensity in emotion expression constitute a risk group for less healthy eating over the lifespan.